2019
DOI: 10.1016/j.gloplacha.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cropping periods of grain crops at the global scale

Abstract: Climate change is posing a challenge to current cropping systems, if production levels are to be maintained or even enhanced. Despite some positive effects that might derive from higher concentrations of CO 2 in the atmosphere, future trends in temperature and precipitation are expected to negatively impact crop productivity (yields and production), especially in regions that are, already today, characterized by high temperatures and water shortages. On

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 230 publications
(490 reference statements)
2
34
0
1
Order By: Relevance
“…Elevated atmospheric carbon dioxide concentrations ([CO 2 ]) on the other hand are expected to increase cotton yields as cotton is a C 3 crop (Kimball, 2016). Numerous free-air carbon dioxide enrichment (FACE) studies demonstrated a strong reaction of cotton yield and growth to an increased CO 2 concentration (Kimball, 1983; Cure and Acock, 1986;Hileman et al, 1994;Hendrix et al, 1994;Reddy et al, 1997;Mauney et al, 1994;Bhattacharya et al, 1994). Likewise, wateruse efficiency can be improved by CO 2 enrichment because it increases biomass and causes partial stomatal closure at the same time, consequently reducing transpiration (Mauney et al, 1994;Hileman et al, 1994;Broughton, 2015; Ko and Piccinni, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated atmospheric carbon dioxide concentrations ([CO 2 ]) on the other hand are expected to increase cotton yields as cotton is a C 3 crop (Kimball, 2016). Numerous free-air carbon dioxide enrichment (FACE) studies demonstrated a strong reaction of cotton yield and growth to an increased CO 2 concentration (Kimball, 1983; Cure and Acock, 1986;Hileman et al, 1994;Hendrix et al, 1994;Reddy et al, 1997;Mauney et al, 1994;Bhattacharya et al, 1994). Likewise, wateruse efficiency can be improved by CO 2 enrichment because it increases biomass and causes partial stomatal closure at the same time, consequently reducing transpiration (Mauney et al, 1994;Hileman et al, 1994;Broughton, 2015; Ko and Piccinni, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous free-air carbon dioxide enrichment (FACE) studies demonstrated a strong reaction of cotton yield and growth to an increased CO 2 concentration (Kimball, 1983; Cure and Acock, 1986;Hileman et al, 1994;Hendrix et al, 1994;Reddy et al, 1997;Mauney et al, 1994;Bhattacharya et al, 1994). Likewise, wateruse efficiency can be improved by CO 2 enrichment because it increases biomass and causes partial stomatal closure at the same time, consequently reducing transpiration (Mauney et al, 1994;Hileman et al, 1994;Broughton, 2015; Ko and Piccinni, 2009). Crop models have been used to assess the effect of changing climate conditions on crop productivity, but the main focus has been on major staple crops -such as maize, wheat, rice, and soybean (e.g., Challinor et al, 2014;Rosenzweig et al, 2014;Müller et al, 2015;Pugh et al, 2016;Schleussner et al, 2018) -that provide the majority of calories to human nutrition (Yahia et al, 2019;Welch and Graham, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although forecasts of future yields reductions can be made with simple statistical models based on regressions in historical weather data, processbased models, which simulate the effect of temperature, water and nutrient availability, and atmospheric CO2 concentration on the process of photosynthesis and the biology and phenology of individual crops, play a critical role in assessing the impacts 20 of climate change.Process-based models are necessary for understanding crop yields in novel conditions not included in historical data, including higher CO 2 levels, out-of-sample combinations of rainfall and temperature, cultivation in areas where crops are not currently grown, and differing management practices (e.g. Pugh et al, 2016;Roberts et al, 2017;Minoli et al, 2019). Processbased models have therefore been widely used in studies on future food security (Wheeler and Von Braun, 2013; Elliott et al, 25…”
mentioning
confidence: 99%
“…Process-based models are necessary for understanding crop yields in novel conditions not included in historical data, including higher CO 2 levels, out-of-sample combinations of rainfall and temperature, cultivation in areas where crops are not currently grown, and differing management practices (e.g. Pugh et al, 2016;Roberts et al, 2017;Minoli et al, 2019). Processbased models have therefore been widely used in studies on future food security (Wheeler and Von Braun, 2013; Elliott et al, 25…”
mentioning
confidence: 99%
“…Cotton is a perennial, indeterminate crop and cultivated species are generally photoperiodic insensitive. Consequently, warmer temperatures will increase the length of growing season if temperature seasonality is the limiting factor (Waha et al, 2012;Minoli et al, 2019) and sufficient water and nutrients are available (Bange and Milroy, 2004;Wang et al, 2008). Hence, one major effect that reduces crop yields in annual crops (Ottman et al, 2012;Asseng et al, 2015) is not as relevant for cotton.…”
mentioning
confidence: 99%